THE IMPACT OF MARKET ATMOSPHERE AND PRODUCT DIVERSITY ON PURCHASE INTENTION: PERCEIVED VALUE AS MEDIATING ROLE: Case Study at Pasar Gembrong Sukasari, Bogor City - Salman Alfarisi; Widi Ruspitasari; Theresia Pradiani (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2025)
This study aims to analyze the impact of market atmosphere and product diversity on consumer purchase intention, with perceived value as a mediating variable, at the newly revitalized Pasar Gembrong Sukasari, Bogor City. Although traditional markets such as Pasar Gembrong Sukasari have fully upgraded their physical facilities, they still encounter competitive challenges and suffer from low consumer purchase intentions, even after revitalization efforts. This study uniquely uses perceived value as a mediating variable to explore the relationship between market atmosphere and product diversity as independent variables and purchase intention as a dependent variable in a revitalized traditional market. Previous studies have shown inconsistent results and rarely integrated all four variables into their analyses. This study addresses this gap by incorporating perceived value. This study, grounded in the Stimulus-Organism-Response (S-O-R) theoretical framework, implemented a quantitative methodology by distributing questionnaires to a purposively selected group of 190 respondents. The collected data were subsequently analyzed using SmartPLS v. 3.2.9 in conjunction with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that market atmosphere (39.1% influence) and product diversity (53.2% influence) significantly impact perceived value. Perceived value, in turn, exerts the most substantial influence on purchase intention (63.4% influence) and plays a significant mediating role in the relationship between environmental stimuli (market atmosphere and product diversity) and purchase intention. Notably, the direct effect of product diversity on purchase intention was found to be insignificant (p-value > 0.05), highlighting the essential role of perceived value as a full mediator. To sustainably boost consumer purchase intentions, efforts to enhance market atmosphere and product diversity should prioritize creating a positive perceived value in consumers' minds.